A Study of Factors Affecting Websites Page Loading Speed for Efficient Web Performance - Manhas, Jatinder (International Journal of Computer Sciences and Engineering, 2013)
This paper analyses trends in page loading time which is an important part of any website’s user experience. And many times we’ll let it slide to accommodate better aesthetic design, new nifty functionality or to add more content to web pages. Unfortunately, website visitors tend to care more about speed than all the bells and whistles we want to add to our websites. Additionally, page loading time is becoming a more important factor when it comes to search engine rankings